PELAKSANAAN PENDAFTARAN TANAH UNTUK PERTAMA KALI BERDASARKAN PERATURAN PEMERINTAH NOMOR 24 TAHUN 1997 TENTANG PENDAFTARAN TANAH (Studi Kasus di Kantor Pertanahan Kabupaten Magetan) - PAMUJI, AGUS (Dinamika Hukum, 2019)
The purpose of this study is to: 1) Review and analyze the implementation of the land register for the first time with the Government Regulation Number 24 year 1997 regarding Land Registration in the Office of land Magetan. 2) review and analyze the obstacles that occur in the implementation of the land register for the first time based on the Government Regulation Number 24 year 1997 regarding Land Registration in the Office of land Magetan. The method of approach in writing this is the juridical sociological. The specification of this research uses descriptive analytic. Data source use the primary data and the data of skunder. Engineering data collection using the study interview, the library and study the documents. To analyze the data, the researchers used a qualitative descriptive methods of analysis. Based on the research results obtained conclusions that: 1) the procedures for the implementation of land registry are sporadic in Magetan Regency sudahsesuai with Government Regulation No. 24 Year 1997. However in practice the implementation of land registry in sporadic yet can increase the amount of land enrolled in Magetan. 2) land registry in sporadic Resistance in Magetan Regency caused by various factors that greatly affect i.e. lack of socialization about the benefits and the land registry, the data provided to the Office for petanahan Register of land does not correspond to the actual data, the number of communities that cannot afford the top large land registration fees, as well as the assumption that the community needed a long time in maintaining the certificate. To overcome the obstacles in the land registry are sporadic in Magetan Regency, such efforts can provide socialization about the benefits of and procedures for the registration of land as a regular activity in the Office of land Office, Magetan The defense is more selective in doing pengecekkan data-the data provided in the activity of the applicant's land registry. Keywords: Land Registration, First.